The evaluation of the modified wave periodization model efficiency on the example of young soccer players' sprint tests - Szymanek-Pilarczyk, M.; Nowak, M. J.; Góra, T.; Oleksy, L.; Drozd, M.; Wasik, J. (Journal of Human Kinetics, 2024)
The research aimed to evaluate the modified model of wave periodization efficiency in running speed tests conducted among soccer players aged 12 to 16. Participants included prospective players of a leading Polish top league soccer club. The research was carried out from 2018 to 2022 in June (Testing A) and December (Testing B) of each year. The test involved 30-m straight line running with 5-, 10-, and 30-m split time measurements. For this purpose, electronic photocells were used (FITLIGHT, Canada). The six-month training intervention increased the athletes' speed as there was a considerable decrease in the running time over the distance of 5 m (F = 7.86; p < 0.001), 10 m (F = 73.99; p < 0.001) and 30 m (F = 127.55; p < 0.001). Analysis of running performance of young soccer players aged 12-16 showed a significant improvement in speed at distances of 5, 10 and 30 m, confirming training effectiveness based on the wave periodization model. The negative correlation between testing year and performance suggests the influence of biological development on players' speed. The COVID-19 pandemic has impacted training, which was reflected in reduced differences between test scores. Improving initial running technique can contribute to better match results, which emphasizes the need for an individual approach to the physical preparation of players.